Facial Nerve Palsy with Total Ophthalmoplegia; a Novel Presentation of Fungal Invasion - Mehdi, Zainab; Bhardwaj , Nidhi; Aggarwal, Jyoti; Kaur, Narinder; Singh, Brijdeep (Archives of Academic Emergency Medicine, 2021)
Mucormycosis is an expeditious invasion of a fungus of angioinvasive nature, predominant in immunocompromised individuals, often leading to organ malfunction and loss. Facial nerve involvement and total ophthalmoplegia are its rare presentations. Early detection and treatment can alter natural disease course and prevent potential catastrophic outcomes in diabetic patients. Facial nerve palsy is mostly attributed to peripheral neuropathy in patients with advanced diabetes mellitus. It rarely raises alarm about an invasive fungal infection. Here, we report the case of a 38-year-old male with type 2 diabetes mellitus, who presented to us with left lower motor neuron type facial palsy and left-sided total ophthalmoplegia due to invasive rhino-orbito-cerebral mucormycosis (ROCM). Despite aggressive measures, including antifungal therapy and repeated endoscopic debridement, he subsequently developed central retinal artery occlusion (CRAO) and underwent left eye exenteration.